Personality characteristics and the decision to hire - Marco Caliendo; Frank M. Fossen; Alexander S. Kritikos (Industrial and Corporate Change, 2022)
As the policy debate on entrepreneurship increasingly centers on firm growth in terms of job creation, it is important to understand whether the personality of entrepreneurs drives the first hiring in their firms. Using the German Socio-Economic Panel (SOEP), we analyze to what extent personality traits influence the probability of becoming an employer. The results indicate that personality matters. Risk tolerance unfolds the strongest influence on hiring, shortening the time until entrepreneurs hire their first employee; the effect size of a one-standard-deviation increase in risk tolerance is similar to that of having a university degree. Moreover, individuals who are more open to experience, more conscientious, and more trustful are more likely to hire upon establishing their business.
Keywords: J22; J23; L26; 330